The Analysis of Quality of Work Life and Work Achievement in Department of Agriculture Simalungun Regency - Nur M. Ridha Tarigan; Rahmat Akbar Syahputra; Tri Kartika Yudha (Budapest International Research and Critics University, 2022)
In fact, the work performance of employees does not match the expectations of an agency, and they still encounter low employee performance. As a result of low employee performance, the impact on agency productivity decreases and cannot meet the targets set by the agency, so that the agency suffers losses and experiences obstacles in its development. Meanwhile, for employees who have low work performance, it will hinder the career development and income of the employee.Descriptive analysis is a research method that provides an overview regarding situations and events so that this method intends to Base data accumulation applies.From the results of the analysis with the number of respondents as many as 63 people, the following conclusions are drawn: 1) Job satisfaction has a positive and significant effect on employee performance in Simalungun Regency Agriculture Office. 2) Leaders are expected to improve the promotion appraisal system based on performance and work results. 3) Maintaining the current good condition of employees, who are able to work hard to get awards, a well-developed family atmosphere and an interesting and challenging work atmosphere has been created.